Corṇapuri Ampikai piḷḷait Tamiḻ - Cuppiramaṇiya Aiyar, Vi. Mu (Makāmakōpāttiyāya Ṭākṭar U. Vē. Cāminātaiyar Nūl Nilaiya veḷiyīṭu, 1982)
Verse work, with critical apparatus, in praise of Corṇapuri Ampikai, form of Pārvati, Hindu deity, enshrined at Tirunangur, Thanjavur District, Tamil Nadu; transcribed from a palm-leaf manuscript preserved in the Maḥamahopadhyaya Dr. U.V. Swaminathaiyar Library, Madras.